Study on Socio-Demographic Characteristics of Alleged Sexual Assault Cases in Rajshahi District in 2020 - Uddin, Md Kafil; Saha, Manasi; Gazi, Md Nasir Uddin; Talukdar, Sandip; Raihan, Mir Md (TAJ: Journal of Teachers Association, 2022)
Introduction: Rape is a neglected public health issue in Bangladesh. Here, the incidence of rape is reported almost every day. However, this study was designed to analyze and explore the statistics of alleged rape cases in the Rajshahi district in 2020. Materials and Methods: This cross-sectional descriptive study was conducted in the Department of Forensic Medicine and Toxicology (DFMT), Rajshahi Medical College (RMC), Rajshahi, Bangladesh, from January 2020 to December 2020. A total of 101 study subjects were included in this study. The data were collected from the alleged rape victims who were sent to the DFMT for medico-legal examination. Informed written consent was signed, and a thumb impression was taken by the victim with her legal guardian when the apparent age of the victim was under 12 years status before data collection. This study explores age, marital status, the pattern of assailants, place of occurrence, religion, opinion based on a physical or genital examination, and corresponding police station with another expert investigative organization such as the Police Bureau of Investigation (PBI) of Rajshahi district. Results: Most of the victims were under 20 years old. Among all victims, 46.53% were unmarried, and 42.57% were married. In maximum cases, the victims were sexually assaulted by the known assailants. Almost two-thirds of alleged rapes occurred in the victim's house and the nearby place of the victim’s house. Only 11.88% of victims were examined with positive signs regarding sexual intercourse. Maximum victims (98.02%) were Muslim. Rape cases were frequent in Godagari, Belpukur, and Chndrima police stations. Conclusion: The findings of this study may work as baseline information and would be constructive in raising social awareness. TAJ 2022; 35: No-1: 45-50